Etika Tabayyun di Era Digital: Melawan Misinformasi dalam Pandangan Islam - Aghisna Khairunnisa; Siti Arum Sari; Rd. Muhamad Hilmi Maulana (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The digital space is currently overwhelmed by misinformation, echo chambers, and hoaxes that threaten the moral fabric of the Muslim community. This library research aims to reconstruct the concept of tabayyun as a modern verification instrument to counter information pathology on social media, as well as to examine its implications instrument for Islamic Religious Education (PAI). Utilizing a qualitative approach and content scientific journals and religious texts were critically analyzed. The findings indicate that tabayyun rooted in prophetic traditions goes beyond mere technical skills; it instills the value of al-anaat (prudence) and spiritual moral responsibility in cyber communication. Furthermore, this study reveals that modern digital logic often prioritizes speed and virality over content authenticity, thereby dulling the netizen’s critical thinking. This curation step is crucial top protect public cognition from the manipulation of negative content, including AI-generated information on timelines. This study concludes that there is an urgent need for Islamic educational institutions to reconstruct the digital literacy curriculum, integrating technical proficiency with prophetic moral ethical values to foster a reflective and non impulsive generation of netizens.